Apolipoprotein M: a novel adipokine decreasing with obesity and upregulated by calorie restriction. Issue 6 (14th March 2019) - Sramkova, Veronika; Berend, Sarah; Siklova, Michaela; Caspar-Bauguil, Sylvie; Carayol, Jérôme; Bonnel, Sophie; Marques, Marie; Decaunes, Pauline; Kolditz, Catherine-Ines; Dahlman, Ingrid; Arner, Peter; Stich, Vladimir; et al.
ABSTRACT: Background: The adipose tissue (AT) is a secretory organ producing a wide variety of factors that participate in the genesis of metabolic disorders linked to excess fat mass. Weight loss improves obesity-related disorders. Objectives: Transcriptomic studies on human AT, and a combination of analyses of transcriptome and proteome profiling of conditioned media from adipocytes and stromal cells isolated from human AT, have led to the identification of apolipoprotein M (apoM) as a putative adipokine. We aimed to validate apoM as novel adipokine, investigate the relation of AT APOM expression with metabolic syndrome and insulin sensitivity, and study the regulation of its expression in AT and secretion during calorie restriction–induced weight loss. Methods: We examined APOM mRNA level and secretion in AT from 485 individuals enrolled in 5 independent clinical trials, and in vitro in human multipotent adipose-derived stem cell adipocytes. APOM expression and secretion were measured during dieting. Results: APOM was expressed in human subcutaneous and visceral AT, mainly by adipocytes. ApoM was released into circulation from AT, and plasma apoM concentrations correlate with AT APOM mRNA levels. In AT, APOM expression inversely correlated with adipocyte size, was lower in obese compared to lean individuals, and reduced in subjects with metabolic syndrome and type 2 diabetes. Regardless of fat depot, there was a positive relation between AT APOM expression and systemic insulin sensitivity, independently of fat mass and plasma HDL cholesterol. In human multipotent adipose-derived stem cell adipocytes, APOM expression was enhanced by insulin-sensitizing peroxisome proliferator–activated receptor agonists and inhibited by tumor necrosis factor α, a cytokine that causes insulin resistance. In obese individuals, calorie restriction increased AT APOM expression and secretion. Conclusions: ApoM is a novel adipokine, the expression of which is a hallmark of healthy AT and is upregulated by calorie restriction. AT apoM deserves further investigation as a potential biomarker of risk for diabetes and cardiovascular diseases.